Reshaping Glocal Dynamics of the Caribbean Relaciones y Desconexiones, Relations et Déconnexions, Relations and Disconnections - Bandau, Anja; Brüske, Anne; Ueckmann, Natascha (Heidelberg University Publishing (heiUP), 2018)
The Circum-Caribbean and its diasporas constitute a space of relations and disconnections. Historically, the Caribbean served as a bridgehead for the European conquest of the Americas and a point of exchange of human beings, ideas, and commodities. It also became a laboratory of modern forms of social, political, and economic production. Today, the region represents a multilingual space of conviviality for many different cultures, but is also the focus of the dissonances, ruptures and insularities produced by its distinct histories of colonialism and resistance. This interdisciplinary volume seeks to explore how (non-)circulation of ideas occurred historically in the glocal production of knowledge in and about the Caribbean and to formulate a clearer picture of who is creating which vision of the Caribbean, and how. The 33 contributions in this volume shed light on the transversal fields of (1) Academic and Artistic Approaches, (2) Arts and Visual Studies, (3) Environment and Sustainability, (4) Migration and Knowledge Circulation, (5) Entangled Histories and Memories.